ANALISIS PENGGUNAAN METODE FUN TEACHING PADA PEMBELAJARAN MATEMATIKA DI KELAS II SDN PENJARINGAN 03 JAKARTA UTARA - Rizka Ezzafira; Yeni Nuraeni; Een Unaenah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study uses a descriptive qualitative method that aims to determine how the use of the Fun Teaching method in mathematics learning in class II SDN Penjaringan 03 North Jakarta. Data collection techniques are carried out through observation, interviews and documentation of teachers and students involved in the learning process. The research process begins with observation of mathematics learning activities in the classroom, then interviews are conducted to obtain more in-depth information about the views of teachers and students on the application of the Fun Teaching method in the classroom. In this method, teachers use various interesting activities such as educational s, singing, guessing words and storytelling to create a fun learning atmosphere and make students more interested in learning. The results of the study show that the Fun Teaching method can increase students' interest in learning and understanding of mathematics material, especially in spatial geometry material. Students become more active, their enthusiasm for learning increases, and the classroom atmosphere becomes more lively. The use of the Fun Teaching method has a positive impact on the mathematics learning process. This method can be an alternative effective learning strategy to improve student learning outcomes in elementary schools Keywords : Learning methods, Fun Teaching , Mathematics